STUDI DRAG FORCE GELOMBANG AIR LAUT TERHADAP FONDASI TIANG MINI (MINIPILE) DI KAWASAN PANTAI PARANGTRITIS - Zainul Faizien Haza (Universitas Sarjanawiyata Tamansiswa, 2015)
Lateral load factor is an important parameter in the calculation of the load capacity of pile foundation, especially in desian pile foundation in coastal areas where the impact of the waves act as additional lateral load that significantly affect to lateral stability of pile foundation, in this case a mini slab foundations (minipile). The interaction between the waves with a pile foundation is a transfer force event, where the force transmitted by waves more as a drag force than impact force. This is because the wave is a fluid material instead of solid material. This study was conducted to determine the magnitude of the drag force due to the waves of the sea water on cylindrical concrete slab foundations mini (minipile). The simulation results show that the use of large diameter pile exacerbated the drag force coefficient of drag force exerted at the same time by the sea water to the surface of minipile